A Hermeneutics of the Kingdom of God in the Context of Armed Conflict in Mindanao - Narciso, Jerson B. (MELINTAS An International Journal of Philosophy and Religion (MIJPR), 2014)
This study attempts to come up with a contextual theological understanding of the biblical concepts of the Kingdom of God in the light of the armed conflict in Mindanao. It seeks to understand the roots and causes of conflict in Mindanao (hermeneutical situation), into which the meaning of the biblical message of a peaceable kingdom is interpreted and understood in a meaningful manner. Taking into account the current socio-political, economic and cultural realities that contribute to the on-going armed conflict in Mindanao, this study raises the issue of how the kingdom of God which embodies God’s love, peace, liberation and justice should be understood and concretized in a way that it could inform and influence the different religious groups and organizations involved in the Mindanao peace process. This attempt for contextualization is based on the principle that theological formulation in the context of conflict in Mindanao, can only be meaningful and intelligible if it reflects critically on the lived-experiences that is shared by different Muslim and Christian communities in Mindanao, especially the poor and marginalized masses in their search for well-being and self-determination.